GAP ANALYSIS (TAX GAP) OF LAND AND BUILDING TAX OF URBAN AND RURAL SECTOR (PBB P2) REVENUES IN KEDIRI CITY - Husaini, Achmad; Dewantara, Rizki Yudhi; Yuniawati, Veny (Jurnal Mahasiswa Perpajakan, 2016)
This study will reveal what makes the gap on the Land and Building Tax of Urban and Rural Sector (PBB P2) revenues in Kediri. PBB P2 is one kind of local taxes which was regulated in Law No. 28 of 2009 on Regional Taxes and Retribution. Kediri is one of cities that had been collecting PBB P2 through Regional Financial Management Body of Kediri (Dispenda Kediri) since the beginning of 2013. This research used descriptive research with qualitative approach. Study’s result shows that tax gap phenomenon is happening in PBB P2 revenues at Kediri. Tax gap itself consists of three variables, they are non-filling gap, underreporting gap, and underpayment gap. All these variables are detected in the PBB P2 revenues in Kediri with different percentage of its variables. Research’s result also shows how Dispenda Kediri didn’t use the tax gap theory to analyze the element of PBB P2 revenues. By knowing the variables contained in tax gap, Dispenda Kediri will be easier to set proper strategies to reduce the amount of tax gap in  PBB P2 revenues. Keywords: Tax Gap, PBB P2, Non-filling Gap, Underreporting Gap, Underpayment Gap